28.1.20 problem 20

Internal problem ID [4326]
Book : Differential equations for engineers by Wei-Chau XIE, Cambridge Press 2010
Section : Chapter 2. First-Order and Simple Higher-Order Differential Equations. Page 78
Problem number : 20
Date solved : Monday, January 27, 2025 at 09:03:18 AM
CAS classification : [_exact, _rational]

\begin{align*} 3 x^{2}+6 x y^{2}+\left (6 x^{2} y+4 y^{3}\right ) y^{\prime }&=0 \end{align*}

Solution by Maple

Time used: 0.020 (sec). Leaf size: 125

dsolve((3*x^2+6*x*y(x)^2)+(6*x^2*y(x)+4*y(x)^3)*diff(y(x),x)=0,y(x), singsol=all)
 
\begin{align*} y \left (x \right ) &= -\frac {\sqrt {-6 x^{2}-2 \sqrt {9 x^{4}-4 x^{3}-4 c_{1}}}}{2} \\ y \left (x \right ) &= \frac {\sqrt {-6 x^{2}-2 \sqrt {9 x^{4}-4 x^{3}-4 c_{1}}}}{2} \\ y \left (x \right ) &= -\frac {\sqrt {-6 x^{2}+2 \sqrt {9 x^{4}-4 x^{3}-4 c_{1}}}}{2} \\ y \left (x \right ) &= \frac {\sqrt {-6 x^{2}+2 \sqrt {9 x^{4}-4 x^{3}-4 c_{1}}}}{2} \\ \end{align*}

Solution by Mathematica

Time used: 6.070 (sec). Leaf size: 163

DSolve[(3*x^2+6*x*y[x]^2)+(6*x^2*y[x]+4*y[x]^3)*D[y[x],x]==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to -\frac {\sqrt {-3 x^2-\sqrt {9 x^4-4 x^3+4 c_1}}}{\sqrt {2}} \\ y(x)\to \frac {\sqrt {-3 x^2-\sqrt {9 x^4-4 x^3+4 c_1}}}{\sqrt {2}} \\ y(x)\to -\frac {\sqrt {-3 x^2+\sqrt {9 x^4-4 x^3+4 c_1}}}{\sqrt {2}} \\ y(x)\to \frac {\sqrt {-3 x^2+\sqrt {9 x^4-4 x^3+4 c_1}}}{\sqrt {2}} \\ \end{align*}